TECHNICAL PERFORMANCE AND EFFICIENCY ANALYSIS OF A 300 KG/H CORN SHELLING MACHINE USING EXPERIMENTAL METHOD - Eka Boangmanalu; Jandri Fan HT Saragi; Angga Bahri Pratama (PT. Radja Intercontinental Publishing, 2026)
This study evaluates the technical performance and efficiency of a corn shelling machine with a capacity of 300 kg/h using an experimental method under field conditions. The research aims to determine machine performance in terms of working capacity, shelling efficiency, unshelled kernels, and total losses. Data were collected through three repeated experimental trials involving measurement of input-output weight and processing time. The results show that the machine operates at a stable capacity of 300 kg/h, consistent with its design specification. The average shelling efficiency reached 94.1%, indicating high separation performance. Unshelled kernels were recorded at 3.3%, while total losses were 2.6%, indicating low material waste. The machine demonstrates effective performance suitable for small to medium-scale corn processing. However, improvements in feeding uniformity and moisture control are recommended to enhance overall efficiency.